The role of short-term memory, type of practice and metacognitive judgments in predicting cognitive offloading - Chiappe, Dan; Vu, Kim-Phuong L.; Tornquist, Michelle (Frontiers in Cognition, 2025)
We examined whether short-term memory (STM) capacity, type of practice, metacognitive judgments and task characteristics influence the likelihood of cognitive offloading. We used a Letter-Naming task, where people hear sets of letters they subsequently must report. We manipulated set size (i.e., 2, 4, 6, 8, and 10 letters) and whether people could write down the letters as they heard them prior to reporting them. We also manipulated the difficulty of the practice trials by varying their set sizes. Consistent with previous studies, we found participants offloaded more as set size increased and that offloading increased accuracy, especially for the higher set sizes. Difficult practice also increased offloading, particularly for smaller set sizes, with many participants developing a perseveration strategy in favor of offloading. Moreover, STM capacity was negatively correlated with frequency of offloading in the intermediate but not in the smallest or largest set sizes. Metacognitive judgments and self-ratings of effort and motivation revealed that although motivation to correctly report the letters predicted overall frequency of offloading, judgments of effort involved in offloading and confidence in task performance did not. Finally, removing the ability to offload also led to lower estimates of short-term memory ability and decreased motivation to correctly report letters.